Prose Elements in the Film the Chronicles of Narnia: The Lion, The Witch, and The Wardrobe by C.S. Lewis. - Kurniati, Nia; Nabila, Azzah; Riqkiyah, Diyana Fauziya (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2025)
The film The Chronicles of Narnia: The Lion, The Witch, and The Wardrobe adapts the novel by C.S. Lewis, brought prose narrative elements into the visual medium. This research aims to analyze the use of prose elements, such as character, plot, setting, theme and symbolism, in conveying moral and spiritual messages to the audience. A descriptive qualitative method with a narrative analysis approach was used to explore these elements. The research results show that this film utilizes prose elements to create a narrative that is not only emotionally deep, but also full of educational messages about sacrifice, courage and hope.